2016
DOI: 10.1002/adma.201601680
|View full text |Cite
|
Sign up to set email alerts
|

A Plasmonic Platform with Disordered Array of Metal Nanoparticles for Three‐Order Enhanced Upconversion Luminescence and Highly Sensitive Near‐Infrared Photodetector

Abstract: Three-order enhanced upconversion luminescence from upconversion nanoparticles is suggested by way of a promising platform utilizing a disordered array of plasmonic metal nanoparticles. Its application toward highly sensitive NIR photodetectors is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
65
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 67 publications
(69 citation statements)
references
References 58 publications
3
65
0
Order By: Relevance
“…As recently reported by our group, [27] the enhanced UCL is based on the combined effects of the expedited internal quantum processes, better NIR absorption, and enhanced nanoantenna effects for forward-scattering of Vis emission. The better NIR absorption in the pNUM configuration is revealed by the absorption spectra ( Figure S3, Supporting Information).…”
Section: Resultsmentioning
confidence: 58%
See 4 more Smart Citations
“…As recently reported by our group, [27] the enhanced UCL is based on the combined effects of the expedited internal quantum processes, better NIR absorption, and enhanced nanoantenna effects for forward-scattering of Vis emission. The better NIR absorption in the pNUM configuration is revealed by the absorption spectra ( Figure S3, Supporting Information).…”
Section: Resultsmentioning
confidence: 58%
“…This abrupt decrease indicates that the radiative decay rate is more effectively boosted by the internal quantum processes in the pNUM configuration [27,28,[35][36][37] than the reference. From the calculation, we found that the radiative decay rate of UCL (Γ r ) is more enhanced by 20.20-(green) and 17.86-times (red) in the weak-excitation regime and 5.52-(green) and 4.88-times (red) in strong-excitation regime for the pNUM configuration than for the UG.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations